Smart Gate System Berbasis Telegram Notification Untuk Peringatan Suhu Tinggi Pada Masa Pandemic Covid-19 - Lestari, Indah Putri; Suroso, Suroso; Salamah, Irma (Patria Artha Technological Journal, 2022)
Covid-19 can spread from individual to individual through droplets of infected individuals. Fever is an early symptom in infected individuals characterized by a rise in body temperature above 37oC. Not a few individuals do not comply with health protocols by not using masks that result in the transmission of Covid-19. This article aims to design and create a Smart gate system that serves to select individuals by identifying the use of masks and checking body temperature without direct contact before entering a room. Body temperature checks are important to be aware of individuals with high body temperatures with the potential for Covid-19 so a warning is required for high-temperature individuals to be checked immediately. The smart gate system is controlled using Arduino Uno R3 and WeMos D1 R32. The research method is the design method. System test results if detected by individuals with high body temperature, smart gate system will send notifications to telegrams and will not give access to individuals with high temperaturesÂ  above 37oC even if they have worn a mask.